Preparation of cemented carbide diamond films by gaseous boronizing pretreatment combines with self-assembly seeding process. (February 2020) - Li, Liang; Wei, Qiuping; Ma, Li; Luo, Yijie; Zhou, Kechao; Yi, Mingkun; Deng, Biao; Chen, Yubo
Abstract: In order to enhance the adhesion of cemented carbide diamond film and improve the cutting performance of cemented carbide diamond coating tools. This paper was the first to combine gaseous boronizing pretreatment with self-assembly seeding process to prepare diamond films on cemented carbide substrate. It not only eliminated the negative influence of cobalt (Co), but also improved the nucleation density of diamond. The gaseous boronizing pretreatment completed the boronation of the cemented carbide in a short time and obtained the CoWB phase which effectively prevented the diffusion of Co. By application of a self-assembly seeding process with the help of [2-(Methacryloyloxy) ethyl] trimethylammonium chloride (TMAEMC) highly improved the colloidal stability of nanodiamond (ND) particles. When the concentration of TMAEMC was 5 × 10 −6  mol/l, the nucleation density of diamond was the highest. Rockwell indentation shows that the combination of gaseous boronizing pretreatment and TMAEMC self-assembly seeding process significantly improved the film-substrate adhesion. The reciprocating friction test shows that the diamond films prepared by this method had low friction coefficient and excellent wear resistance. Therefore, gaseous boronizing pretreatment combines with self-assembly seeding process is an effective way to achieve strong adhesion and high cutting performance of industrial diamond coating tools. Highlights: Combining gaseous boronizing pretreatment with self-assembly seeding process to prepare diamond film on cemented carbide. The gaseous boronizing pretreatment obtained the CoWB phase which effectively prevented the diffusion of Co. By application of a self-assembly seeding nanodiamond process highly improved the nucleation density of diamond. The results showed that the diamond film prepared by this method had good adhesion and low friction coefficient.